Q methodology: an overview and steps to implementation / Siti Maftuhah Damio - Damio, Siti Maftuhah (Universiti Teknologi MARA, 2016)
The research methodology known as Q Methodology is relatively unknown in the Malaysian sphere. Nonetheless, if you are uncovering ‘points of view’ held around a topic, Q Methodology is one of the methods to consider. There are seven (7) steps in Q Methodology implementation which combine both qualitative and quantitative methods. The aim of this article is to give an overview and steps to implementation of Q Methodology. Q Methodology, in this article is exemplified through a study on the conceptions of Autonomy in Language Learning.